2004
DOI: 10.1111/j.1365-2648.2004.02983.x
|View full text |Cite
|
Sign up to set email alerts
|

Informal carers’ experience of caring for stroke survivors

Abstract: A public health campaign to educate and inform that stroke is a medical emergency is required if stroke disability is to be minimized. The use of new technologies should be considered in facilitating carers' learning how to care. There is a need to test alternative models of stroke follow-up in multi-centre studies that are holistic and place the carer-stroke survivor at the centre of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
0
20

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(177 citation statements)
references
References 25 publications
13
144
0
20
Order By: Relevance
“…10 In this study 68.4% of HCPs identified a need to know more about advising carers and/or relatives on personality changes. This is in line with research elsewhere that has found that personality changes in the post stroke survivor often make relatives feel as if they are "living with a stranger" (Smith et al 2004) We are unclear why more HCPs than doctors wanted further knowledge on the assessment and management of post-stroke depression. Perhaps doctors felt confident in managing depression or they may have seen it as another HCP's role.…”
Section: Clinical Knowledge In Strokesupporting
confidence: 73%
“…10 In this study 68.4% of HCPs identified a need to know more about advising carers and/or relatives on personality changes. This is in line with research elsewhere that has found that personality changes in the post stroke survivor often make relatives feel as if they are "living with a stranger" (Smith et al 2004) We are unclear why more HCPs than doctors wanted further knowledge on the assessment and management of post-stroke depression. Perhaps doctors felt confident in managing depression or they may have seen it as another HCP's role.…”
Section: Clinical Knowledge In Strokesupporting
confidence: 73%
“…Research demonstrates that stroke survivors and their caregivers often lack the information necessary to help manage the recovery process at home [23][24]. Many stroke caregivers lack basic information about strokes, strategies for caring for stroke survivors, and ways to prevent complications and future strokes.…”
Section: Stroke Caregivingmentioning
confidence: 99%
“…Care giving is a very important task that post-stroke disabled patients understand very little and the informal caregivers make an important contribution to supply disabled stroke survivors at home 15,16 . Previous researches demonstrate that stroke survivors and their caregivers often lack the information necessary to help manage the recovery process at home 17,18 . Moreover, informal caregivers face the dual challenge of coming to terms with the sudden onset and subsequent disabling impact of stroke and the realization that the person may require long-term support 19 .…”
Section: Introductionmentioning
confidence: 99%